PEMBERIAN GUANO WALET DENGAN PENGURANGAN PUPUK SP-36 TERHADAP PERTUMBUHAN DAN HASIL TANAMANKUBIS BUNGA (Brassica oleracea var.botrytis L.) PADA TANAH SPODOSOL (The Application Of Guano Walet With Reduction Of SP-36 Fertilizer To Growth And Yield Of Flower: Rohman1), Candra, B.1), Zubaidah, S.1) - Admin journal (Fakultas Pertanian Universitas Palangka Raya, 2019)
ABSTRACTThe aim of this study was to determine the interaction between guano walet administration and reduction of SP-36 fertilizer on growth and yield of flower cabbage; to find out the effect of guano walet on the growth and yield of flower cabbage; and to find out the effect of SP-36 fertilizer reduction on growth and yield of flower cabbage. The study was conducted from May to August 2018. This study used a completely randomized design (CRD) consisting of 2 factors namely guano walet with a reduction in SP-36 fertilizer, 4 x 4 factorial pattern with 3 replications. The variables observed were the number of leaves, flowering age, plant wet weight, fresh weight of flowers, and diameter of flower crop. The results showed that the combination of 100% guano walet administration with a reduction of SP-36 0% on spodosol soil gave the best results for the number of leaves with an average value of 16.00 strands at 6 weeks after planting and fresh flower weight of 166, 76 g. Guano walet administration on spodosol soil with a dose of 100% gave the best results on the number of leaves by 25.83 strands at the age of 9 weeks after planting, flowering age of 79.33 day, plant wet weight of 326.82 g and the results showed that the combination of 100% guano walet administration with a reduction of SP-36 0% gave the best results for the diameter of flower cropwith an average value of 12,15 cm.Key words: cabbage flower, guano walet, SP-36 fertilizer, spodosolsABSTRAKTujuan dari penelitian ini adalah untuk mengetahui interaksi antara pemberian guano walet dengan pengurangan pupuk SP-36 terhadap pertumbuhan dan hasil kubis bunga; untuk mengetahui pengaruh pemberian guano walet terhadap pertumbuhan dan hasil kubis bunga; dan untuk mengetahui pengaruh pengurangan pupuk SP-36 terhadap pertumbuhan dan hasil kubisbunga.Penelitian dilaksanakan mulai dari bulan Mei sampai Agustus 2018. Penelitian ini menggunakan rancangan acak lengkap (RAL) yang terdiri dari 2 faktor, yaitu pemberian guano walet dengan pengurangan pupuk SP-36, pola faktorial 4 x 4 dengan 3 ulangan. Variabel yang diamati adalah jumlah daun, umur berbunga, bobot segar total tanaman, bobot segar bunga, dan diameter krop bunga. Hasil penelitian menunjukkan bahwa kombinasi pemberian guano walet 100% dengan pengurangan SP-36 0% pada tanah spodosol memberikan hasil terbaik jumlah daun dengan nilai rata-rata sebesar 16,00 helai tanaman-1 pada umur 6 minggu setelah tanam dan bobot segar bunga 166,76 g tanaman-1. Pemberian guano walet pada tanah spodosol dengan dosis 100% memberikan hasil terbaik terhadap jumlah daun sebesar 25,83 helai tanaman-1 pada umur 9 minggu setelah tanam, umur munculnya bunga pada hari ke- 79,33, bobot segar total tanaman sebesar 326,82 g tanaman-1dan pada variabel diameter krop bunga pemberian guano 50% dengan pengurangan pupuk SP-36 0% memberikan hasil sebesar 12,15 cm tanaman-1.Kata kunci: Guano walet, kubis bunga, pupuk SP-36, tanah spodosol